2016
DOI: 10.1016/j.powtec.2015.11.059
|View full text |Cite
|
Sign up to set email alerts
|

Fluid bed film coating of fine ibuprofen particles

Abstract: Fine pharmaceutical powders pose significant challenge in fluid bed (FB) film coating due to their high cohesion. Ibuprofen powders, considered as model Geldart group C powders with Sauter mean diameters of 41 m (coarse) and 22 m (micronized), could not be fluidized due to severe agglomeration, solid-bridging, and poor flowability. Dry coating, applied as a pre-processing method that coats nano-silica on the surface of ibuprofen, enabled sufficiently improved flow, hence fluidization via reduced cohesion. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…shows the morphology and three dimension image of CMK-3 and CMK-5 observed by SEM. The aggregates of CMK-3 and CMK-5 as can be observed in SEM images show three dimension size of 0.5x3x10 µm 3 and 0.1x2x10 µm3 , respectively.The shape of CMK-3 was observed as a noodle-like structure but CMK-5 appeared as a bunch of noodle-like structure with overlapping parts in the whole surface. The CMK-3 morphology is similar to CMK-5 with small differences in mouth pore and overlapping sites.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…shows the morphology and three dimension image of CMK-3 and CMK-5 observed by SEM. The aggregates of CMK-3 and CMK-5 as can be observed in SEM images show three dimension size of 0.5x3x10 µm 3 and 0.1x2x10 µm3 , respectively.The shape of CMK-3 was observed as a noodle-like structure but CMK-5 appeared as a bunch of noodle-like structure with overlapping parts in the whole surface. The CMK-3 morphology is similar to CMK-5 with small differences in mouth pore and overlapping sites.…”
mentioning
confidence: 82%
“…In ibuprofen research of drug delivery model, it was reported that the adsorption method is the most effective technique to remove this organic molecule drug as a pollutant in the aquatic area [3]. The previous report has been used activated carbon as adsorbent not only for ibuprofen but also for another organic pollutant [4].…”
Section: Ico-helicsmentioning
confidence: 99%
“…[13][14][15] Surface modification is a method for improving the cohesiveness and flowability of APIs using a small amount of additives. 16) The surface modification method can alleviate problematic properties by coating the surface of API particles with fine-particle excipients or water-soluble polymers. In particular, the dry surface modification method is a simple coating method that involves simply mixing a drug and an excipient; several studies describing such methods have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these issues, conventional methods can be optimized by improving the particles or modifying the fluidized bed. Thereby, powders can be granulated with larger particles in order to enhance the fluidization, drying and coating process in the fluidized bed [13]. Otherwise, fluidization can also be assisted by a variety of mechanisms such as vibration, mechanical agitation, sound and magnetic force to improve the flowability of cohesive particles [6,14,15].…”
Section: Introductionmentioning
confidence: 99%